Sensory Qualities as Signs? Meyer Schapiro as a Pioneer of the Semiotics of ‘Visual Form’ - Andersson, Fred (Semiotika, 2023)
The concept and nature of Form in linguistic as well as visual signs has been debated among several semioticians and art historians. Some notable analytical attempts have been put forward by Saussure, Hjelmslev, Vygotsky, and, regarding visual signs in particular, by Meyer Schapiro, Floch, Greimas, and the Groupe µ, among others. Greimas and Floch proposed a distinction between two levels of semiotic Form in visual representation, each being constitutive of a separate system of semiotic articulation: figurative language and plastic language. With arguments drawn from behavioural science, the interdisciplinary Groupe µ presented a different version of the same distinction as one between iconic and plastic signs. In this paper, I shall give a short outline of these and some further proposals, especially Meyer Schapiro’s view on the formal structure of pictures and visual signs, and his analysis of visual signifiers as ‘vehicles’ of spatial meaning. Schapiro’s account of the ‘image-sign’ will be presented as coloured by his socio-historical perspective and the empirical pragmatism of Peirce. Regarding the relationship between ‘iconic’ and ‘plastic’ meaning, Schapiro’s studies of Romanesque sculpture and non-figurative painting anticipate some observations later made by the Groupe µ. However, rather than attempting to defend any specific account of the nature of visual or plastic Form, a pluralistic position will be proposed here.